The Immune Response to Sand Fly Salivary Proteins and Its Influence on Leishmania Immunity - Gomes, Regis; Oliveira, Fabiano (Frontiers in Immunology, 2012)
Leishmaniasis is a vector-borne disease transmitted by bites of phlebotomine sand flies. During Leishmania transmission, sand fly saliva is co-inoculated with parasites into the skin of the mammalian host. Sand fly saliva consists of roughly thirty different salivary proteins, many with known roles linked to blood feeding facilitation. Apart from the anti-hemostatic capacity of saliva, several sand fly salivary proteins have been shown to be immunogenic. Immunization with a single salivary protein or exposure to uninfected bites was shown to result in a protective immune response against leishmaniasis. Antibodies to saliva were not required for this protection. A strong body of evidence points to the role for saliva-specific T cells producing IFN-γ in the form of a delayed-type hypersensitivity reaction at the bite site as the main protective response. Herein, we review the immunity to sand fly salivary proteins in the context of its vector–parasite–host combinations and their vaccine potential, as well as some recent advances to shed light on the mechanism of how an immune response to sand fly saliva protects against leishmaniasis.